2021
DOI: 10.1016/j.aninu.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Zinc alleviates the heat stress of primary cultured hepatocytes of broiler embryos via enhancing the antioxidant ability and attenuating the heat shock responses

Abstract: Zinc (Zn) has been shown to attenuate the adverse effects of heat stress on broilers, but the mechanisms involving this process remain unclear. We aimed to investigate possible protective mechanisms of Zn on primary cultured hepatocytes of broiler embryos subjected to heat stress. Three experiments were conducted. In Exp. 1, hepatocytes were treated with 0, 50, 100, 200, or 400 μmol/L added Zn as inorganic Zn sulfate (iZn) for 12, 24 or 48 h. In Exp. 2, cells were exposed to 40 °C (a normal temperature [NT]) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
0
17
1
Order By: Relevance
“…CuZn-SOD and MT are considered as endogenous ROS scavengers that confer protection against oxidative stress in vivo [ 38 , 39 ]. Related studies have shown that heat stress can lead to increased CuZn-SOD and MT mRNA abundance expression in hepatocytes [ 40 ]. Against our experimental results, this may be due to the destructive effect of excessive ROS on post-transcriptional Nrf2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CuZn-SOD and MT are considered as endogenous ROS scavengers that confer protection against oxidative stress in vivo [ 38 , 39 ]. Related studies have shown that heat stress can lead to increased CuZn-SOD and MT mRNA abundance expression in hepatocytes [ 40 ]. Against our experimental results, this may be due to the destructive effect of excessive ROS on post-transcriptional Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, zinc plays an important role under heat stress conditions. Zinc can effectively attenuate the heat-shock responses with down-regulated expressions of HSP70 mRNA in broilers [ 40 ]. Meanwhile, zinc can also adjust abnormal levels of the MDA and 8-OHdG in tissue and serum to decrease the oxidative damage caused by heat stress in broilers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 24 d treatments with various P concentrations, the mRNA expression levels of local bone-derived regulator genes ( FGF23, MEPE, DMP1 and PHEX ) and BMP/MAPK pathway-related genes [BMP2, extracellular signal-regulated kinase 1 (ERK1), c-Jun N-terminal kinase 1 (JNK1) and p38 mitogen-activated protein kinase alpha (p38α)] were evaluated by real-time quantitative polymerase chain reaction (RT-qPCR) as described by Li et al ( 31 ). Briefly, according to the manufacturer's instruction, PrimeScriptTM RT Master Mix kit (TaKaRa, Dalian, China) was used to reverse RNA into cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for PCR was as follows: denaturation at 95°C for 2 min followed by 40 cycles of 95°C for 60 s, 60°C for 30 s, and 72°C for 30 s. The geometric means of β -actin and glyceraldehyde 3-phosphate dehydrogenase ( GAPDH ) were used as references to normalize the expression of the target gene. The internal references and calculation of the relative mRNA expression for MnSOD target gene were used as described previously ( Li et al., 2021 ). The primer sequences are listed in Table 3 .…”
Section: Methodsmentioning
confidence: 99%